Anhydride structures affect the acylation modification and emulsion stabilization ability of mammalian and fish gelatins. (1st May 2022) - Zhang, Ting; Xu, Jiamin; Huang, Shudan; Tao, Ningping; Wang, Xichang; Zhong, Jian
Highlights: Anhydrides with different carbon numbers were applied to modify gelatins. Degree of acylation decreased with the increase of ring sizes or side chain lengths. Surface hydrophobicity increased with the increase of anhydride carbon numbers. Emulsion droplet size decreased with the increase of anhydride carbon numbers. Emulsion stability was dependent on gelatin type and anhydrides. Abstract: In this work, ring-like anhydrides (C4, C5, and C6) with different sizes and succinic anhydrides (C4, C10, C12, C14, and C16) with different side chain lengths were used to modify bovine bone gelatin (BBG) and cold-water fish skin gelatin (CFG), and the effect of acylated gelatins on fish oil-loaded emulsions stability was explored. The results showed that the degree of N -acylation decreased with increased ring sizes or side chain lengths, and the surface hydrophobicity of acylated gelatins increased with increased anhydride carbon numbers. Acylated CFGs had higher droplet stability and lower liquid-gel transition time than acylated BBGs. Only BBG-C12 had a slight increase on the creaming stability among these acylated gelatins. These results demonstrated that the gelatins could be modified by all the anhydrides and their emulsion stabilization ability was dependent on the gelatin type and anhydride structure. The results could be beneficial for protein-based emulsifier development and application.